(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
This research sheds light on Ibn Al-Farid’s great Ta’i poem, as a comprehensive model for the Sufi thought that prevailed in the Mamluk era on the one hand, and the creative intensity that characterized the literature of that era on the other. Especially that this Ta’i yyah named (the behavior organized) have marked obscure its meanings and included a system from so mystical term which reveal about the mystical experience in general, and Ibn Al-Farid’s journey in his sufi miraj particularly. The research concluded that the Badiiyyah formations were an aid to Ibn al-Farid in expressing his mystical experience, that is contributed to discovering on his sufi thought and his technical prowess, especially when they achieved harmony in semantic performance on the one hand, and add to his poetry trinket rhetorical and rhythmic, the two levels phonemic and semantic overlap, on the other